Konflik Masyarakat dan Perusahaan Desa Motoduto Kecamatan Boliyohuto Kabupaten Gorontalo - Pilonguli, Fitriyanti; Ibrahim, Ridwan; Hatu, Dewinta Rizky R. (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2023)
This study aims to find out how the conflict that occurred between the community and the company, PT. Tri Jaya Tangguh, occurred in Motoduto Village, Boliyohuto District, Gorontalo Regency. The problem faced is community and company conflict, which was triggered by environmental pollution due to industrial wastewater that was channeled directly into the river and flowed into neighboring villages. The liquid waste discharged into the river creates a pungent smell; the color is brownish, and the odor from the waste disturbs the community around the company. The method used in this study is a qualitative method using a descriptive approach. Data collection techniques using observation, interview, and documentation techniques. The results showed that the conflict that occurred between the community and the company was triggered by environmental pollution due to industrial wastewater that was channeled into the river and created a pungent, brown odor. The smell from the sewage disturbs community activities in the study location. Besides that, a conflict resolution plan has been designed in which the company provides compensation in the form of an amount of money to the community; however, this compensation is considered by the community to have not been able to resolve the problems at the study site. The conflict that is happening at this time raises the determinants of conflict that do not get a solution. Until the end of this study, the problems at the study location had not found a meeting point.